Emergent high-temperature superconductivity at interfaces. (May 2020) - Song, Can-Li; Ma, Xu-Cun; Xue, Qi-Kun
Abstract: Abstract : Low-dimensional superconductors have been at the forefront of physics research due to their rich physical properties such as high-temperature ( T c ) superconductivity. In this article, we review the field of emergent high- T c superconductivity at interfaces of heterostructures, focusing on the experimental advances and its physical mechanism. Charge transfer between constituent materials leads to two-dimensional carrier confinement that facilitates occurrence of superconductivity at the interface. We discuss the similarities between bulk high-Tc superconductors and interface systems, as well as implications from a survey of interface superconductors. We expect that the hybrid heterostructures and the ability to manipulate them on an atomic scale could be an enormously fertile ground to explore superconductivity with higher critical temperature T c .